Formation and development of media literacy in Kazakhstan (Herald of Journalism, 2018)
The article highlights the concept of media literacy in the information sphere, which is one of themost important issues to date, and provides information on the development of the media in Kazakhstan.In the field of information, there are many facts about illiteracy, which today lead to a multitude of problems,including interethnic conflicts. A common understanding of media and information for democracyis described. And it also talks about media components and options for using it to efficiently and quicklyaccess information. How should we today be critical of information and information sources. The articledescribes in detail the application of new and traditional media formats in Kazakhstan. One of themain goals of this article is to introduce the functions of the media and other information services andto realize their importance for developing a civilian position and making decisions taking into accountall available information. Demonstrate knowledge and understanding of various ways of using media inpersonal and professional life.
Keywords: fake, fact-check, democracy, range, competence, convergence in the media industry, media literacy, drone-journalism, media hygiene, discrimination, longrida, infographic.; Түйінсөздеp: фейк, фaкт-чекинг, демокрaтия, диaпaзон, компетенция, медиaиндустриядaғы конвергенция, медиaсaуaттылық, дрон-журнaлистикa, медиaгигиенa, дискриминaция, лонгридтер, инфогрaфикa.